2017
DOI: 10.5603/cj.a2016.0112
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the presence of chronically occluded coronary artery on long-term prognosis of patients with acute ST-segment elevation myocardial infarction

Abstract: Background: Multivessel disease (MVD) is a significant risk factor in patients with acute ST-segment elevation myocardial infarction (STEMI (OR 2.07, p = 0.002), whereas triple vessel disease was not (OR 1.27, p = 0.358). The other independent predictors of mortality were: age, anterior myocardial infarction, and PCI failure. Conclusions:The presence of CTO is an independent predictor of the long-term mortality in STEMI patients treated with primary PCI. (Cardiol J 2017; 24, 2: 117-124)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…ird, nearly 84% of our study population were male. Although this might not reflect the real world, this phenomenon did prevail across other previous studies [2,6,7,11,12,20]. And our result showed the predictive capability of CTO in the non-IRA only in the male subgroup.…”
Section: Limitationscontrasting
confidence: 41%
See 2 more Smart Citations
“…ird, nearly 84% of our study population were male. Although this might not reflect the real world, this phenomenon did prevail across other previous studies [2,6,7,11,12,20]. And our result showed the predictive capability of CTO in the non-IRA only in the male subgroup.…”
Section: Limitationscontrasting
confidence: 41%
“…Similarly, Ariza-Sole et al contended CTO in the non-IRA did not act as an independent predictor of 1-year mortality on 1176 STEMI patients [2]. Lesiak et al performed the longest 6-year follow-up study on 836 STEMI patients and supported CTO in the non-IRA's predictive role [6]. Last but not least, O'Connor et al carried out a meta-analysis encompassing 11451 STEMI patients from 7 observational studies and showed CTO in the non-IRA was independently associated with increased mortality at a mean follow-up of 25.2 months [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation